Situation of snakebite, antivenom market and access to antivenoms in ASEAN countries. Issue 3 (16th March 2022) - Patikorn, Chanthawat; Ismail, Ahmad Khaldun; Abidin, Syafiq Asnawi Zainal; Blanco, Francis Bonn; Blessmann, Jörg; Choumlivong, Khamla; Comandante, John David; Doan, Uyen Vy; Mohamed @ Ismail, Zainalabidin; Khine, Yi Yi; Maharani, Tri; Nwe, Myat Thet; et al.
Abstract : Introduction: Snakebite envenoming is a neglected tropical disease posing public health challenges globally. The Association of Southeast Asian Nations (ASEAN) countries are among the tropical regions with disproportionately high incidence of snakebite. Hence, this study aimed to review the situation of snakebite, antivenom market and access to antivenoms in ASEAN. Methods: This mixed-methods study included comprehensive literature review and in-depth interviews with key informants to assess the situation of management system of snakebite, antivenom market and access to antivenoms in seven ASEAN countries, including Malaysia, Thailand, Indonesia, Philippines, Vietnam, Lao PDR and Myanmar. Data were analysed by a framework method. Results: ASEAN have developed various strategies to improve outcomes of snakebite victims. Five domestic antivenom manufacturers in the region produce up to 288 375 vials of antivenoms annually with the value of US$13 058 053 million which could treat 42 213 snakebite victims. However, there remain challenges to be addressed especially the lack of snakebite-related informatics system, inadequate antivenoms at the healthcare facilities and when the majority of snakebite victims seek traditional healers instead of conventional treatment. Conclusion: Improving the situation of snakebite and antivenom is not only about the availability of antivenom, but the whole landscape of surrounding management and supporting system. The assessment of the situation of snakebite and antivenom is crucial for countries or regions where snakebites are prevalent to recognise their current standpoint to inform the development of strategies to achieve the goal set by the WHO of halving the global burden of snakebite by 2030.